Synthesis of novel 5-aryl-2-thio-1,3,4-oxadiazoles and the study of their structure-anti-mycobacterial activities - Macaev, Fliur Zainutdin; Rusu, Ghenadie G.; Pogrebnoi, Serghei I.; Gudima, Alexandru P.; Stingaci, Eugenia; Vlad, Liudmila A.; Shvets, Nathaly M. (My University, 2005)
The preparation of novel 5-aryl-2-thio-1,3,4-oxadiazoles 4a-41 and the computer-aided study of their in vitro anti-tubercular activity against Mycobacterium tuberculosis H37Rv (ATCC 27294) are reported. The average accuracy of the electronic-topological method and neural network methods applied to the activity prediction in leave-one-out cross validation is 80%. © 2005 Elsevier Ltd. All rights reserved. © 2008 Elsevier B.V., All rights reserved.; MEDLINE® is the source for the MeSH terms of this document.
Keywords: 5-Aryl-2-thio-1,3,4-oxadiazoles; Anti-tubercular activity; Electronic-topological method; Neural network method; Structure-activity relationships